Synthesis and biological evaluation for some metal complexes with a new ligand (E)-3-(((2-amino-4-methylphenyl)imino)methyl)-4H-chromen-4-one - Adel Salim; Jinan Mohammed Mahmood Al-Zinkee; Areej Ali Jarullah (Academic Science Journal)
Complexes of Co(II),  Ni(II), Cu(II)  Zn(II),  and Cd (II) with the ligand 3-(((2-amino-4-methylphenyl)imino)methyl)-4H-chromen-4-one  derived 3-formyl chromone with 4-methyl-O-phenylenediamine were synthesized and characterized by elemental analysis, FTIR,  electronic spectra,  magnetic moment and molar conductance. The prepared complexes have the general formulae [M(C17H14N2O2)2]Cl2, M = Co(II), Ni(II),  Cu(II) and  Zn(II) except complex of cadmium it have the formulae [Cd(C17H14N2O2)Cl]Cl.  The data which obtain from  analysis indicate  that  the complexes have octahedral geometry around the metal center except cadmium complex exhibit tetrahedral geometry. Two types of bacteria (E.coli ) and (S. aureus ) used to estimate the biological activities of complexes .